SISTEM AGRIBISNIS TANAMAN HIAS BUNGA (Adenium, Anggrek, dan Mawar) DI KOTA BANDAR LAMPUNG - Filipus Cahya Kusuma Putra; Yaktiworo Indriani; Maya Riantini (Lampung University, 2021)
This study aims to analyze the process of procuring production facilities in accordance with the right six (on time, place, quality, quantity, type, and price), farm performance, the marketing efficiency of the agribusiness system, and the supporting institutions for ornamental flower agribusiness systems at Lampung. This study uses a survey method conducted in the city of Bandar Lampung, namely in Gunung Terang, Gunung Agung and in the Way Halim Permai. Sampling in this study was sixteen respondents taken using a quota sampling technique. Data collection was carried out in September - October 2019. The results showed that the procurement of production facilities of ornamental flower plant farming had fulfilled the right six. Ornamental flower farming in Bandar Lampung is feasible to be cultivated because in farming it has an R / C ratio> 1, that is, the R / C over the total cost of 1.70 of adenium flowers, 2.00 of orchids, and 1.60 of roses. The three ornamental flower plants studied have a profit margin ratio of more than 1 which is 1.41 of the adenium flower, 1.80 of the orchid flower, and 1.81 of the rose flower, which means that the ornamental flower farmers in Bandar Lampung receives profits and no loss. Supporting institutions in the flower plant agribusiness system at the research location are financial institutions, namely banks as financing and borrowing funds, government policies, and transportation. All these supporting institutions are available but have not been used optimally by farmers.Key words: agribusiness system, R/C, profit margin ratio